Changes in liver metabolic pathways demonstrate efficacy of the combined dietary and microbial therapeutic intervention in MASLD mouse model - Iannone V; Babu AF; Lok J; Gómez-Gallego C; D'Auria G; Vazquez-Uribe R; Vaaben TH; Bongers M; Mikkonen S; Vaittinen M; Tikkanen I; Kettunen M; et al. (Elsevier BV, 2025)
Objective: Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), is the most prevalent liver disease globally, yet no therapies are approved. The effects of Escherichia coli Nissle 1917 expressing aldafermin, an engineered analog of the intestinal hormone FGF19, in combination with dietary change were investigated as a potential treatment for MASLD.
Methods: MASLD was induced in C57BL/6J male mice by American lifestyle-induced obesity syndrome diet and then switched to a standard chow diet for seven weeks. In addition to the dietary change, the intervention group received genetically engineered E. coli Nissle expressing aldafermin, while control groups received either E. coli Nissle vehicle or no treatment. MASLD-related plasma biomarkers were measured using an automated clinical chemistry analyzer. The liver steatosis was assessed by histology and bioimaging analysis using Fiji (ImageJ) software. The effects of the intervention in the liver were also evaluated by RNA sequencing and liquid-chromatography-based non-targeted metabolomics analysis. Pathway enrichment studies were conducted by integrating the differentially expressed genes from the transcriptomics findings with the metabolites from the metabolomics results using Ingenuity pathway analysis.
Results: After the intervention, E. coli Nissle expressing aldafermin along with dietary changes reduced body weight, liver steatosis, plasma aspartate aminotransferase, and plasma cholesterol levels compared to the two control groups. The integration of transcriptomics with non-targeted metabolomics analysis revealed the downregulation of amino acid metabolism and related receptor signaling pathways potentially implicated in the reduction of hepatic steatosis and insulin resistance. Moreover, the downregulation of pathways linked to lipid metabolism and changes in amino acid-related pathways suggested an overall reduction of oxidative stress in the liver.
Conclusions: These data support the potential for using engineered microbial therapeutics in combination with dietary changes for managing MASLD.
Keywords: Aldafermin; Genetically modified E.coli Nissle 1917; Non-alcoholic fatty liver disease; Non-targeted metabolomics; Omics integration; Transcriptomics.